Distribution of raphespinal fibers in the mouse spinal cord - Liang, H.; Wang, S.; Francis, R.; Whan, R.; Watson, Charles; Paxinos, G. (BioMed Central, 2015)
Background: Serotonergic raphespinal neurons and their fibers have been mapped in large mammals, but the non- serotonergic ones have not been studied, especially in the mouse. The present study aimed to investigate the termination pattern of fibers arising from the hindbrain raphe and reticular nuclei which also have serotonergic neurons by injecting the anterograde tracer BDA into them. Results: We found that raphespinal fibers terminate in both the dorsal and ventral horns in addition to lamina 10. There is a shift of the fibers in the ventral horn towards the dorsal and lateral part of the gray matter. Considerable variation in the termination pattern also exists between raphe nuclei with raphe magnus having more fibers terminating in the dorsal horn. Fibers from the adjacent gigantocellular reticular nucleus show similar termination pattern as those from the raphe nuclei with slight difference. Immunofluorescence staining showed that raphespinal fibers were heterogeneous and serotoninergic fibers were present in all laminae but mainly in laminae 1, 2, medial lamina 8, laminae 9 and 10. Surprisingly, immunofluorescence staining on clarified spinal cord tissue revealed that serotoninergic fibers formed bundles regularly in a short distance along the rostrocaudal axis in the medial part of the ventral horn and they extended towards the lateral motor neuron column area. Conclusion: Serotonergic and non-serotonergic fibers arising from the hindbrain raphe and reticular nuclei had similar termination pattern in the mouse spinal cord with subtle difference. The present study provides anatomical foundation for the multiple roles raphe and adjacent reticular nuclei play.